Engaging Learners through Data: Senso Eskwela Pilipinas - Tolentino, Mark Anthony C (Archīum Ateneo, 2022)
The use of real data in teaching and learning statistics has been recommended in the literature. This paper talks about the development and implementation of the Senso Eskwela Pilipinas, the first database in the Philippines that builds and provides real data with the intention of making the study of statistics engaging, understandable, relatable, and relevant for Filipino learners